Model Cooperative Learning Tipe Make A Match Untuk Meningkatkan Hasil Belajar Dan Aktivitas Siswa - Rilda Weni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
This study was conducted as solution for the low learning activity and achievement of 5th grade students at SDN 21 Batang Anai Kabupaten Padang Pariaman. The low learning activity and achievement of students was caused by teaching process which often to use expository method. This study is a classroom action research with two cycles aimed to improve students’ learning activity and achievement by implementing one of cooperative learning model, i.e. make a match type. Subjects of this study are 5th grade students at SDN 21 Batang Anai. Mean of test score of students in cycle I is 60.00 and become 76.88 in cycle II. Students’ learning activity was also improved. Thus, cooperative learning –make a match- can improve students’ learning activity and achievement.